The Alaskan laundry - Jones, Brendan (Boston : Mariner Books, Houghton Mifflin Harcourt, 2016)
"A fresh debut novel about a lost, fierce young woman who finds her way to Alaska and finds herself through the hard work of fishing, as far as the icy Bering Sea Tara Marconi has made her way to "The Rock," a remote island in Alaska governed by the seasons and the demands of the world of commercial fishing. She hasn't felt at home in a long while -- her mother's death left her unmoored and created a seemingly insurmountable rift between her and her father. But in the majestic, mysterious, and tough boundary-lands of Alaska she begins to work her way up the fishing ladder -- from hatchery assistant all the way to King crabber. She learned discipline from years as a young boxer in Philly, but here she learns anew what it means to work, to connect, and -- in buying and fixing up an old tugboat -- how to make a home she knows is her own. A beautiful evocation of a place that can't help but change us and a testament to the unshakable lure of home, The Alaskan Laundry also offers an unforgettable story of one woman's journey from isolation back to the possibility of love. "--
"A Mariner original."
Keywords: Women fishers -- Fiction; Fish trade -- Alaska -- Fiction; Self-realization in women -- Fiction; Alaska -- Fiction; Fiction